Rational Pharmacotherapy for Sore Throat in Children at Different Stages of the Assistance - A.V. Zaychenko; Ye.N. Kovalenko; T.A. Bryukhanova (Zaslavsky O.Yu., 2013)
The article deals with one of the most pressing problems in pediatrics in the autumn and winter - a sore throat in children. The authors give its basic reasons, threatening symptoms that accompany sore throat, indicating an urgent need to visit a doctor, as well as the issues of treatment. It is noted that the most appropriate is the use of combination drugs that have complex (anti-microbial, anti-inflammatory, analgesic) effect. The characteristics of Strepsils Kids preparation, developed specifically for use in children from 6 years, are given.